Tunable single- and dual-wavelength fiber ring lasers using an Er-Yb doped waveguide amplifier - Peng, PC; Chi, S (My University, 2005)
We demonstrate tunable single- and dual-wavelength fiber ring lasers using a compact Er-Yb doped waveguide amplifier. In the single-wavelength operation, a signal-to-noise ratio higher than 63 dB and an output power maintaining around 11 dBm in the operation range over 50 nm (from 1529.1 to 1579.43 nm) are achieved. In the dual-wavelength operation, lasing wavelengths with wavelength separation from 51.73 to 6.2 nm are demonstrated. (c) 2005 Society of Photo-Optical Instrumentation Engineers.
Keywords: fiber ring laser; dual-wavelength laser; tunable laser; Er-Yb doped waveguide amplifier